Capacities and gaps in Caribbean fisherfolk organization leadership. (1st December 2022) - Pena, Maria; McConney, Patrick; Perch, Leisa; Phillips, Terrence
Abstract: Organizational leadership is one of the most important roles for both women and men in the fishing industry. Empowerment of fisherfolk organization and strengthening or development of their capacity, especially in relation to leadership, is important to the successful implementation of the 2014 Voluntary Guidelines for Securing Sustainable Small-Scale Fisheries in the Context of Food Security and Poverty Eradication (SSF Guidelines) and the realization of sustainable fisheries and stewardship. Leadership is a challenging and relatively recent fisheries research topic, and gender is poorly documented in Caribbean fisheries. The deficiency of knowledge on leadership and gender was addressed through fisherfolk organization leader assessments to assist in understanding capacities and gaps in Caribbean fisherfolk organization leadership for informing gender and other aspects of overall SSF Guidelines implementation. Our work contributes to a baseline of knowledge on fisher organization leaders in the region. It confirms some already known information on fisherfolk organizations, documenting this and new information. Dimensions such as decision-making, gender, participation, governance, education and assets relevant to fisherfolk leadership are covered in the leadership profile developed. We discuss the implications of this preliminary and exploratory applied research for Caribbean fisheries in the context of the SSF Guidelines, and a way forward.